Cost-effectiveness analysis of anlotinib plus chemotherapy with or without benmelstobart versus chemotherapy alone for extensive-stage small-cell lung cancer in China - You, Caicong; Zhang, Jiahao; Lei, Jianying; Fu, Wu; Zheng, Bin; Liu, Maobai; Li, Na (Frontiers in Oncology, 2024)
ObjectivesThe ETER701 trial demonstrated that benmelstobart combined with anlotinib and etoposide-carboplatin (EC) significantly extends survival in patients with extensive-stage small cell lung cancer (ES-SCLC), setting a new record for median overall survival. In contrast, anlotinib plus EC only significantly prolongs progression-free survival. However, there is currently no evidence evaluating the cost-effectiveness of these regimens as first-line treatments. Therefore, this study assesses the cost-effectiveness of these three first-line treatment options from the perspective of the Chinese healthcare system.MethodsA time-varying Markov model was constructed to simulate the disease progression of a 62-year-old patient with ES-SCLC, assessing direct medical costs, health benefits, and incremental cost-effectiveness ratios (ICER). Both flexible and standard parametric models were included to fit and extrapolate survival data. The probabilities, costs, and health utilities required for the model were sourced from literature, databases, and expert consultations. Additionally, sensitivity and scenario analyses were conducted to explore the impact of various parameters on model uncertainty.ResultsCompared to EC alone, the combination of benmelstobart, anlotinib, and EC added $80,879.12 in cost for 0.7288 quality-adjusted life years (QALYs), an ICER of $110,970.19/QALY. Anlotinib plus EC added $4,107.86for 0.1951 QALYs, an ICER of $21,056.19/QALY. At a $37,598/QALY threshold, the cost-effectiveness probability for benmelstobart combination is 0%, and for anlotinib combination is 80.42%. A 73.79% price cut for benmelstobart is needed for cost-effectiveness.ConclusionsIn China, benmelstobart combined with anlotinib and EC is not a cost-effective first-line treatment for ES-SCLC; however, reducing the price of benmelstobart by 73.79% could make this regimen cost-effective. In contrast, anlotinib combined with EC may represent a more cost-effective first-line treatment option.